Analisis Sidang Sengketa Pajak oleh Pengadilan Pajak yang Dilaksanakan Diluar Daerah Jakarta Ditinjau dari Azas Ease of Administration - Khoiry, Lukmanul Hakim Al; Rahayu, Ning (Jurnal Ilmiah Administrasi Publik, 2020)
The implementation of the tax dispute trial is regulated by the Law of The Republic of Indonesia No.14/2002 concerning Tax Court article 4 which states that the tax dispute trial conducted by the tax court can be held in Jakarta and other regions if it is deemed necessary. The problem arises when local taxpayers whose tax dispute trials are held outside Jakarta hire a tax consultant from Jakarta, the taxpayer must bear the transportation and accomodation costs of the tax consultant team who come to the region where the trial is held, such as airline tickets, hotels, and other costs during the trial. The tax court institution also bear the travel cost of the official team of tax court judges who will lead the trial, because the judge who leads the trial comes from Jakarta. This study aims to analyze the implementation of tax dispute trial held outside Jakarta in terms of the principle of ease of administration. The results show that in terms of the four ease of administration principles, only the principle of efficiency is not fulfilled. This is due to the high costs incurred by taxpayers and tax courts side to conduct tax dispute trials outside Jakarta.